Radical Trachelectomy for the Treatment of Early-Stage Cervical Cancer: A Systematic Review - Smith, Evan S. (Obstet Gynecol, 2020)
OBJECTIVES: To assess surgical, oncologic, and pregnancy outcomes in patients undergoing radical vaginal, abdominal, or laparoscopic trachelectomy for the treatment of early-stage cervical cancer, using a methodic review of published literature. DATA SOURCES: PubMed, Embase, and Cochrane Library sources, including ClinicalTrials.gov, were searched from 1990 to 2019 with terms “cervical cancer” and “(vaginal, abdominal, open, minimally invasive, or laparoscopic) radical trachelectomy”. Grey literature and unpublished data were omitted. METHODS OF STUDY SELECTION: After removal of duplicates from a combined EndNote library of results, 490 articles were reviewed using Covidence software. Two reviewers screened titles and abstracts, and then screened full texts. Selection criteria included articles reporting radical trachelectomy with lymph node assessment as primary therapy for cervical carcinoma, with stated follow-up intervals and recurrences. TABULATION, INTEGRATION, AND RESULTS: Variables of interest were manually extracted into an electronic database. A total 47 articles reporting on 2566 women met inclusion criteria. Most tumors were of squamous histology (68.5%), stage IB1 (74.8%), <2cm (69.2%), and without lymphovascular invasion (68.8%). Of planned trachelectomies, 9% were converted intraoperatively to hysterectomy. Separated by route of trachelectomy, 58.1%, 37.2%, and 4.7% were performed using radical vaginal, abdominal, and laparoscopic approaches, respectively. With median follow-up of 48 months (range 2-202 months) across studies, median recurrence rate was 3.3% (range 0-25%); median time to recurrence was 26 months (range 8-44 months). Median 5-year recurrence-free and overall survival were 94.6% (range 88-97.3%) and 97.4% (range 95-99%), respectively. The post-trachelectomy pregnancy rate was 23.9% with a live birth rate of 75.1%. CONCLUSIONS: Radical trachelectomy for fertility-preserving treatment of cervical cancer is widely reported in the literature, though publications are mainly limited to case reports and case series. Reported follow-up periods infrequently meet standard oncologic parameters but show encouraging recurrence-free and overall survival rates and pregnancy outcomes. Higher-level evidence needed for meta-analysis is lacking.